Spurring Innovation with Matching Grants : Evidence from Yemen - McKenzie, David (2015)
Matching grants are one of the most common tools used in private sector development programs in developing countries and have been included in more than 60 World Bank projects totaling over US$1.2 billion, funding over 100,000 micro, small and medium enterprises. The Enterprise Revitalization and Employment Pilot (EREP) was designed as a two year pilot project aimed at improving firm capabilities and the employability of recent graduates. The matching grant component provided firms with a matching grant of up to $10,000 as a 50 percent subsidy towards the cost of innovation and business services like finance and accounting systems, website creation, training, marketing, participation in exhibitions, and some associated goods. The program implementation was designed with the lessons of other matching grant programs in mind in order to overcome their problems with take-up: eligibility criteria were kept broad; the application form was not complex and could be done either online or in paper; and the program was well-advertised.